Development of FIVAROM-NET: Inclusive Learning Media for Fire Evacuation of Blind Students at SLBN Semarang - Jamal, Jamal Isnan; Suharini, Erni; Hayati, Rahma (Yayasan Ilomata, 2024)
There were 938 cases of fire disasters in Central Java in 2021 and Semarang City was in first place with 162 cases. SLBN Semarang, which is located in the city of Semarang, certainly needs effective learning media to increase disaster knowledge. This research aims to develop Fivarom-net, a braille-based fire disaster evacuation map learning media. The fulfillment of facilities and accessibility is the main urgency to increase knowledge and get to know the space in the school environment. This research uses a research and development approach with ADDIE's development design consisting of analysis, design, development, implementation, and evaluation. Data analysis consists of qualitative and quantitative data analysis. The results of observation of learning media at SLBN Semarang are still minimal and inadequate for teaching and learning activities for visually impaired students in mobility-oriented learning. Fivarom-net learning media was developed to produce a better understanding of space through the concept of maps that adjust the learning characteristics of visually impaired students. The analysis of media effectiveness was calculated by calculating the average assessment of three aspects from media experts obtained a figure of 90.67% and from material experts of 84%. Thus, Fivarom-net media is declared effective for the learning of visually impaired students in understanding the surrounding space, especially evacuation routes. This research can increase literacy and knowledge in the field of learning media that are in accordance with the learning characteristics of visually impaired students. In addition, this research contributes to the world of education for children with special needs.